(untitled) (Global Journal of Human-Social Science, 2012)
The research aimed at developing model of the risk assurance indicators to the utilization of natural resources and environment for sustainable development of Thai communities and evaluation of risks indicators on natural recourses and environment for sustainability of life quality, economy, and society. Mixed research methodology-both quantitative and qualitativewas employed to collect data from the various sources, related documents experts, and indigenous group from three villages-namely, upper north (Nan), central north (Uttaradit), and lower north (Pijit) with 10 villages of each to construct and validate the hypothetical indicators. A multi-stage sample size was included 80 community experts, 140 general experts, 350 community leaders, and 407 family delegates in Northern Thailand to evaluate the practicality and appropriateness of the constructed risk assurance indicators. The data were collected by group discussion, deep interview, and questionnaires.